Photoinduced free radical polymerization initiated with quinoxalines - Arsu, N; Aydin, M (WILEY-V C H VERLAG GMBH, 1999)
Quinoxaline and substituted quinoxalines were used as photoinitiators with N-methyldiethanolamine and 2-(N-methyl-N-phenylamino)-1-phenylethanol as co-initiators for the polymerization of methyl methacrylate. The rates of polymerization were in the range 10(-4)-10(-6) mol L(-1) s(-1). Air inhibition was remarked on the rate of polymerization of methyl methacrylate in the absence of amines.
Keywords: Polymer Science